Using a smartphone-based self-management platform to support medication adherence and clinical consultation in Parkinson's disease. (December 2017) - Lakshminarayana, Rashmi; Wang, Duolao; Burn, David; Chaudhuri, K.; Galtrey, Clare; Guzman, Natalie; Hellman, Bruce; Ben James,; Pal, Suvankar; Stamford, Jon; Steiger, Malcolm; Stott, R.; et al.
Abstract The progressive nature of Parkinson's disease, its complex treatment regimens and the high rates of comorbid conditions make self-management and treatment adherence a challenge. Clinicians have limited face-to-face consultation time with Parkinson's disease patients, making it difficult to comprehensively address non-adherence. Here we share the results from a multi-centre (seven centres) randomised controlled trial conducted in England and Scotland to assess the impact of using a smartphone-based Parkinson's tracker app to promote patient self-management, enhance treatment adherence and quality of clinical consultation. Eligible Parkinson's disease patients were randomised using a 1:1 ratio according to a computer-generated random sequence, stratified by centre and using blocks of variable size, to intervention Parkinson's Tracker App or control (Treatment as Usual). Primary outcome was the self-reported score of adherence to treatment (Morisky medication adherence scale −8) at 16 weeks. Secondary outcomes were Quality of Life (Parkinson's disease questionnaire −39), quality of consultation for Parkinson's disease patients (Patient-centred questionnaire for Parkinson's disease ), impact on non-motor symptoms (Non-motor symptoms questionnaire), depression and anxiety (Hospital anxiety and depression scale) and beliefs about medication (Beliefs about Medication Questionnaire) at 16 weeks. Primary and secondary endpoints were analysed using a generalised linear model with treatment as the fixed effect and baseline measurement as the covariate. 158 patients completed the study (Parkinson's tracker app = 68 and TAU = 90). At 16 weeks Parkinson's tracker app significantly improved adherence, compared to treatment as usual (mean difference: 0.39, 95%CI 0.04–0.74;p  = 0.0304) with no confounding effects of gender, number of comorbidities and age. Among secondary outcomes, Parkinson's tracker app significantly improved patients' perception of quality of consultation (0.15, 95% CI 0.03 to 0.27;p  = 0.0110). The change in non-motor symptoms was −0.82 (95% CI −1.75 to 0.10;p  = 0.0822). 72% of participants in the Parkinson's tracker app group continued to use and engage with the application throughout the 16-week trial period. The Parkinson's tracker app can be an effective and novel way of enhancing self-reported medication adherence and quality of clinical consultation by supporting self-management in Parkinson's disease in patients owning smartphones. Further work is recommended to determine whether the benefits of the intervention are maintained beyond the 16 week study period. Digital healthcare: App helps patients stick to plan A smartphone-based application improves treatment adherence of patients with Parkinson's disease (PD). Rashmi Lakshminarayana, from uMotif Ltd, and researchers from the UK and The Netherlands describe the results of a 16 week trial of a Parkinson's tracker app (PTA) that randomised 215 patients from seven different health centres. Patients using the app reported significantly better adherence to their medication plan compared with control patients who continued their treatment as usual. Interestingly, using the PTA also improved the patients' perception of the quality of their clinical care, possibly as a result of feeling more involved and in control of their care. These findings suggest that by sending medication reminders and tracking symptoms, the app can help patients with Parkinson's self-manage their increasingly complex treatment regimen as the disease progresses.